PENERAPAN TEORI BEHAVIORISME DALAM MENINGKATKAN DISIPLIN DAN KOGNISI DASAR SISWA DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAR - Syah, Pirman; Taslim, Muh.; Hasma; Arifuddin, Kartini Annisa; Damopolii, Muljono; Saprin (Prodi PGMI IAI Sahid, 2026)
This study aims to examine the application of behaviorism theory in improving students' discipline and basic cognitive abilities in science learning in elementary schools. The study focuses on stimulus-response-based learning strategies, particularly through repeated practice (drill), direct reinforcement, and providing rapid and specific feedback. This study uses a qualitative approach with a literature review method. Data were collected through searching scientific documents obtained from various sources such as Tandfonline, Routledge, ERIC, Google Scholar, Academia, and national repositories, with the keywords